(untitled) (Itinera, 2018)
Walter Benjamin’s texts on Baudelaire put forward a threefold analogy, surprising at first glance, between the experience of the crowd, typical of modern metropolises, mechanized work and games of chance. While exploring gambling and the gambler in Benjamin’s analysis, this article explores the inner ambiguity of the concept of repetition: firstly conceived as belonging to the «time of hell» of the ever-new, it can also be understood as a gateway for understanding the processes of experimentation, which are crucial to modern and contemporary aesthetic experiences. In this sense, urban space can also be conceived as a room for play, vulnerable to and enriched by chance and playful mechanisms encompassing aesthetic and political dimensions.